2007
DOI: 10.1021/ja075785o
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Regioselectivity in Palladium-Catalyzed Cross-Coupling Reactions of Polyhalogenated Heterocycles

Abstract: Sequential cross-coupling on multihalogenated heterocycles is a particularly attractive strategy for the divergent synthesis of polysubstituted heterocycles, but the factors that govern the regioselectivity are not well understood. The present study shows that the selectivity in palladium-catalyzed cross-coupling reactions of heterocycles bearing multiple identical halogens is determined by both the energy to distort the carbon halogen bond to the transition-state geometry (related to BDE) and the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(178 citation statements)
references
References 23 publications
2
173
0
1
Order By: Relevance
“…For dihalobenzenes, the reaction preferentially occurs at the carbon-halogen bond bearing the less electron-rich carbon [16]. For dihaloheteroarenes, detailed studies have been conducted [17], and the site-selectivity has been found to be determined by factors, such as the strengths of the carbon-halogen bonds and the coefficients of the heterocycle π* (LUMO) [18,19].…”
Section: Open Accessmentioning
confidence: 99%
“…For dihalobenzenes, the reaction preferentially occurs at the carbon-halogen bond bearing the less electron-rich carbon [16]. For dihaloheteroarenes, detailed studies have been conducted [17], and the site-selectivity has been found to be determined by factors, such as the strengths of the carbon-halogen bonds and the coefficients of the heterocycle π* (LUMO) [18,19].…”
Section: Open Accessmentioning
confidence: 99%
“…[9] They showed, for instance, how the activation barrier of S N 2 reactions originates from steric congestion around the carbon atom that is nucleophilically attacked, and how electronic factors modulate the barrier height. [9,10] Not much later, Houk et al [11] were the first to successfully apply the activation strain model (or distortion/interaction model) to pericyclic reactions, in particular to [3+2] cycloaddition reactions. The latter, curiously, are concerted and occur through highly synchronous and in-plane aromatic transition states, very similar to the situation for DGT reactions.…”
Section: Introductionmentioning
confidence: 99%
“…the interactions between the catalyst and the organo-halide and the BDEs) are usually at play. [65][66][67] To better understand the regioselectivity in the OA of (2b), we performed some detailed calculations. We used the aldimine (2b), with the Ms-group, instead of Ts-or Ns to reduce the conformational complexity.…”
Section: -61mentioning
confidence: 99%